Current applications and prospects of visceral fat in obesity diagnosis and comorbidity prediction - ZHANG Yifei, SHI Juan, XU Yuening (Zhenduanxue lilun yu shijian, 2025)
In 2021, 2.11 billion adults aged 25 and older worldwide were overweight or obese, with China having the highest number at 402 million. By 2050, the global population of overweight or obese adults is projected to rise to 3.8 billion, with China expected to account for 627 million of this total. Moreover, obesity is strongly associated with the occurrence and progression of various diseases, including cardiovascular diseases, cancers, and type 2 diabetes. Thus, the diagnosis and management of obesity have become a major global health challenge. However, traditional body mass index (BMI)-based diagnostic systems exhibit limitations in accurately reflecting abnormal fat distribution and metabolic dysfunction. Excessive visceral fat accumulation has been identified as a key factor in obesity-related metabolic disorders. Notably, visceral fat area (VFA), as an objective and quantifiable indicator for obesity assessment, demonstrates significant correlations with obesity and its comorbidities. Recent studies show that VFA outperforms BMI in the diagnosis and prediction of obesity and its associated comorbidities. Furthermore, VFA demonstrates superior value in evaluating the therapeutic efficacy of different interventions for obesity. Experience from China's Metabolic Management Center (MMC) has demonstrated the clinical value of VFA measured by standardized bioelectrical impedance analysis in obesity diagnosis and clinical mana-gement. In the future, the diagnosis and clinical management of obesity and its comorbidities should integrate multiple assessment methods incorporating multidimensional stratification analysis and personalized precision evaluation to further enhance comprehensive clinical management of obesity.